PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Novianti, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study was to examine the effect of company size, capital structure, profitability, and liquidity on firm value The sample used in the study amounted to 66 companies with a total of manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017 using purposive sampling method. The data obtained is then processed using software E-Views version 10.0. Research shows that profitability has an effect on company value, firm size, capital structure, and liquidity does not affect the value of the company.